Simple Multitasking Sensors-Actuators-Transducers Based on Arduino - Nanang Suwondo, Hassan K. Juwhari, Dwi Sulisworo (International Journal of Advanced Science and Technology, 2020)
The use of a smart and simple sensor in physics education is increasing rapidly. The purpose of thispaper is to describe the development of simple multitasking sensors, actuators, and transducers.Instrumentation multitasking sensors, actuators, and transducers have been developed based onArduino mega 2560 with FreeRTOS_AVR. Commands and data are transmitted and received wirelessserially by Arduino and laptop through the Bluetooth module. Then, the results are displayed in theform of graphical icons, and visual indicators made using Processing 3. It allows the environment tointeract with the system. The results show that visual assessment has been confirmed with the systemperforming as designed to do. Besides, the developed software code is proven suitable for installationon the Arduino MEGA2560.